2021
DOI: 10.3390/ma14185197
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion-Based 3D Printing of Calcium Magnesium Phosphate Cement Pastes for Degradable Bone Implants

Abstract: This study aimed to develop printable calcium magnesium phosphate pastes that harden by immersion in ammonium phosphate solution post-printing. Besides the main mineral compound, biocompatible ceramic, magnesium oxide and hydroxypropylmethylcellulose (HPMC) were the crucial components. Two pastes with different powder to liquid ratios of 1.35 g/mL and 1.93 g/mL were characterized regarding their rheological properties. Here, ageing over the course of 24 h showed an increase in viscosity and extrusion force, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…As previously described in studies on CMPCs with the application form of granules, pastes or cylindrical scaffolds (Wu et al, 2008b;Wei et al, 2010;Ewald et al, 2019;Fuchs et al, 2021;Götz et al, 2021;Kowalewicz et al, 2021), the CMPCs investigated in this study as well as TCP showed excellent clinical tolerability with physiological wound healing. No animal showed lameness or pain.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…As previously described in studies on CMPCs with the application form of granules, pastes or cylindrical scaffolds (Wu et al, 2008b;Wei et al, 2010;Ewald et al, 2019;Fuchs et al, 2021;Götz et al, 2021;Kowalewicz et al, 2021), the CMPCs investigated in this study as well as TCP showed excellent clinical tolerability with physiological wound healing. No animal showed lameness or pain.…”
Section: Discussionsupporting
confidence: 65%
“…Due to their better mechanical properties as well as their faster degradation compared to CPCs, CMPCs have been increasingly researched in recent years in the form of cement pastes and granules ( Wu et al, 2008a ; Wu et al, 2008b ; Klammert et al, 2010a ; Jia et al, 2010 ; Wei et al, 2010 ; Vorndran et al, 2011 ; Zeng et al, 2012 ; Ewald et al, 2019 ; Fuchs et al, 2021 ; Götz et al, 2021 ). However, for the treatment of many bone defects, three-dimensional, dimensionally stable scaffolds are required, that can be produced patient-specifically.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the compressive strength found for the different strand spacings in this work, as well as in the previously published work by our group, which was in connection with inverse 3D printing with variations in the strand width of the resulting scaffolds for use as a bone replacement [ 45 ]. Götz et al [ 46 ] also described the decrease in compressive strength with increasing strand spacing. In their work, however, they investigated scaffolds made of calcium magnesium phosphate cement.…”
Section: Discussionmentioning
confidence: 99%
“…Since Mg is a common substitute for Ca in natural bone tissue, so Mg-based materials are often added into CaP cement to form MCP cement to increase their setting time and mechanical properties. 20,79,80…”
Section: Magnesium Phosphate Cementsmentioning
confidence: 99%